2020
DOI: 10.1128/jcm.01109-20
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as an Alternate Specimen Source for Detection of SARS-CoV-2 in Symptomatic Patients Using Cepheid Xpert Xpress SARS-CoV-2

Abstract: Among the many facets of the SARS-CoV-2 pandemic is the unprecedented pressure it has placed on different points of the supply chain for hospital systems worldwide such as collection devices for the diagnosis of COVID-19.…

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(181 citation statements)
references
References 0 publications
14
164
0
2
Order By: Relevance
“…Here, we present evidence for the clinical usefulness of saliva specimens in diagnosing COVID-19. Previous studies reported that the sensitivity of RT-qPCR-analyzed saliva specimens was 69.2-100% for COVID-19 compared with the initial diagnosis using throat and nasopharyngeal swabs initially collected from hospitalized patients (12)(13)(14)(15)(16)(17)(18)20). The difference in sensitivity probably reflects differences in the clinical background and timing of sampling in each study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Here, we present evidence for the clinical usefulness of saliva specimens in diagnosing COVID-19. Previous studies reported that the sensitivity of RT-qPCR-analyzed saliva specimens was 69.2-100% for COVID-19 compared with the initial diagnosis using throat and nasopharyngeal swabs initially collected from hospitalized patients (12)(13)(14)(15)(16)(17)(18)20). The difference in sensitivity probably reflects differences in the clinical background and timing of sampling in each study.…”
Section: Discussionmentioning
confidence: 96%
“…Previously reported sensitivities of RT-qPCR assays were lower for upper respiratory specimens (32-61% for pharyngeal swabs and 63-73% for nasopharyngeal swabs) than they were for lower respiratory specimens (72-93% for sputum and 93-100% for bronchoalveolar lavage fluid) (9)(10)(11). Recently, several reports highlighted the clinical usefulness of RT-qPCR analysis of saliva specimens (12)(13)(14)(15)(16)(17)(18). Saliva specimens can be easily collected by the patients themselves by spitting into a collection tube; thus, using saliva specimens can reduce the burden on a patient, reduce the risk of exposure to viral droplets for medical workers, and reduce the time (1.38-fold shorter) and cost (2.09-fold lower) of the testing procedure compared to using nasopharyngeal swabs (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that the relative sensitivity of self-collected saliva specimens compared with nasopharyngeal specimens is more than 85% [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. However, the methods and instructions on collection varied between the studies and the optimal method remains uncertain, from gargling with saline solutions, spitting, collection of drools, or use of pipet of special sponges [ 18 , 19 , 22 , [24] , [25] , [26] , [27] ]. The use of deep-throat saliva, which is the self-collection of the posterior oropharyngeal secretion, was particularly studied in depth.…”
Section: Specimen Typesmentioning
confidence: 99%
“…In the following weeks, other studies investigated the role of saliva as a diagnostic tool by also recruiting symptomatic patients with a milder form of the disease ( Becker et al 2020 ; Caulley et al. 2020 ; Iwasaki et al 2020 ; Jamal et al 2020 ; Kim, Lee, et al 2020 ; McCormick-Baw et al 2020 ; Migueres et al. 2020 ; Nagura-Ikeda et al 2020 ; Pasomsub et al 2020 ; Williams et al 2020 ; Wyllie et al 2020 ).…”
Section: The Detection Of Sars-cov-2 In Salivamentioning
confidence: 99%